Efficiency of pain inhibition and facilitation of fibromyalgia patients is not different from healthy controls: Relevance of sensitivity-adjusted test stimuli. Issue 2 (April 2023) - Staud, Roland; Godfrey, Melyssa M; Riley, Joseph L; Fillingim, Roger B
Background: Pain is a dynamic phenomenon dependent on the balance of endogenous excitatory and inhibitory systems, which can be characterized by quantitative sensory testing. Many previous studies of pain modulatory capacity of patients with fibromyalgia syndrome (FM) have reported decreased pain inhibition or increased pain facilitation. This is the first study to assess pain modulation, including conditioned pain modulation (CPM) and temporal pain summation, in the same healthy control (HC) and FM participants. Methods: Only sensitivity-adjusted stimuli were utilized for testing of conditioned pain modulation (CPM) and temporal pain summation in 23 FM patients and 28 HC. All subjects received sensitivity-adjusted ramp-hold (sRH) during testing of pain facilitation (temporal summation) and pain inhibition (CPM). CPM efficacy was evaluated with test stimuli applied either concurrently or after application of the conditioning stimulus. Finally, the effects of CPM on pressure pain thresholds were tested. Results: FM subjects required significantly less intense test and conditioning stimuli than HC participants to achieve standardized pain ratings of 50 ± 10 numerical rating scale (NRS) ( p = 0.03). Using such stimuli, FM subjects' temporal pain summation and CPM efficacy was not significantly different from HC (all p > 0.05), suggesting similar pain facilitation and inhibition. Furthermore, the CPM efficacy of FM and HC participants was similar regardless of whether the test stimuli were applied during or after the conditioning stimulus ( p > 0.05). Conclusion: Similar to previous studies, FM participants demonstrated hyperalgesia to heat, cold, and mechanical stimuli. However, using only sensitivity-adjusted stimuli during CPM and temporal summation testing, FM patients demonstrated similarly effective pain inhibition and facilitation than HC, suggesting that their pain modulation is not abnormal.